Effectiveness Comparison of Aloe vera and 70% Alcohol Hand Sanitizers in Reducing Hand Microorganism Colonies - Yunanda, Laurenz Diffa; Masfiyah, Masfiyah; Rahayu, Rahayu (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Microbe-based infection transmission commonly occurs through hands, as hands harbor both normal microbiota and pathogenic microorganisms. The use of hand sanitizer is preferred by the public due to its practicality compared to handwashing. However, alcohol-based hand sanitizers can cause irritation and dryness of the skin. The availability of natural ingredient-based hand sanitizers remains limited. This study aims to analyze the difference in effectiveness between aloe vera-based hand sanitizer and 70% alcohol hand sanitizer in reducing the number of microorganism colonies on hands. This experimental study employed a Pre-Post Test Group Design. Samples were consecutively sampled from medical students at Sultan Agung Islamic University, Semarang, using the glove juice method, with 20 samples per group. The percentage reduction in microorganism colony counts between the aloe vera-based hand sanitizer group and the 70% alcohol group was analyzed using the Mann-Whitney test. The results showed that the mean effectiveness in reducing microorganism colony counts after using alcohol-based hand sanitizer was 59.2%, while that of the aloe vera-based hand sanitizer was 37.97%. The Mann-Whitney test yielded a p-value of 0.001 (p < 0.05). There is a significant difference in the effectiveness of aloe vera-based hand sanitizer compared to 70% alcohol hand sanitizer in reducing microorganism colony counts on hands. The 70% alcohol-based hand sanitizer was found to be more effective than the aloe vera-based formulation.